THE REPRESENTER METHOD FOR TWO-PHASE FLOW IN POROUS MEDIA - Baird J.; Dawson C. (My University, 2007)
The representer method is applied to a one-dimensional two-phase flow model in porous media; capillary pressure and gravity are neglected. The Euler–Lagrange equations must be linearized, and one such linearization is presented here. The representer method is applied to the linear system iteratively until convergence, though a rigorous proof of convergence is out of reach. The linearization chosen is easy to calculate but does not converge for certain weights; however, a simple damping restores convergence at the cost of extra iterations. Numerical experiments are performed that illustrate the method, and quick comparison to the ensemble Kalman smoother is made.
Keywords: REPRESENTER METHOD; TWO-PHASE FLOW; POROUS MEDIA; ENSEMBLE KALMAN SMOOTHER